Implementation of Roleplaying Method to Train Speaking Skill of Students of Mandarin Language Education Universitas Negeri Malang - Amani, Fienita; Retnantiti, Sawitri; Ventivani, Aiga (Universitas Negeri Malang, 2024)
This study aims to describe the application of the roleplaying method to train the speaking skills of students of Mandarin Language Education Study Program State University of Malang. The theme of this roleplaying method is 学校 (school) with eight dialogs, namely (1) 新学生 (New Student), (2) 老师 (Teacher), (3) 介绍 (Introduction), (4) 上课 (Lesson), (5) 汉语 (Chinese), (6) 休息 (Break Time), (7) 学习 (Study), and (8) 作业 (Doing Assignment). This research uses a descriptive qualitative approach. The data sources in this study were 32 students of the Chinese Language Education Study Program Class of 2022. The results showed that the application of the roleplaying method in research activities went well. The results of the assessment and evaluation of the roleplaying dialog showed that most students were fluent in Chinese dialog although there were some mistakes in pronunciation of tone and intonation. Students stated that the roleplaying method was able to make students feel confident and help train students' Chinese language skills, especially in speaking and grammar skills, and make learning interesting and fun.